Development of a Personal Financial Information System via the LINE Application - พลอยแดง, ศิริโชติ; สาระเดช, เมธา; นาคสุข, พุทธินันท์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to develop a personal financial information system via the LINE application to record daily income and expenses. The system was designed and developed by applying chatbot technology as a user interface, working in conjunction with an automated intermediary processing system. This system systematically extracts and classifies data conditions, and stores the processed information in Google Sheets. The target group in this study consisted of 30 general individuals who regularly use the LINE application in their daily lives, selected through purposive sampling. The research instruments included: 1) a chatbot system via a LINE Official Account and a cloud-based database management system using Google Sheets; 2) a system efficiency evaluation form assessed by experts; and 3) a user satisfaction questionnaire.            The research findings indicated that the system is capable of systematically collecting, storing, processing, and displaying personal spending behavior data. It can summarize key information such as total income, total expenses, and overall balances. The system efficiency, evaluated by experts, was rated at a high level with a mean score of 4.13 and a standard deviation of 0.63. In addition, user satisfaction, assessed by 30 users, was also at a high level with a mean score of 4.26 and a standard deviation of 0.61. Therefore, the system can be effectively utilized for recording income and expenses, as well as summarizing daily financial data in a simpler, more convenient, and faster manner.